Dual-stage adaptive control of hybrid energy storage system for electric vehicle application. (November 2021) - Arslan, Muhammad; Ahmad, Iftikhar; Azeem, Muhammad Kashif; Liaquat, Muwahida
Abstract: In this research contribution, adaptive terminal sliding mode control (ATSMC) of the hybrid energy storage system (HESS) has been proposed having fuel cell as a major source and ultra-capacitor as an auxiliary source of energy. ATSMC has been proposed to control the switching operation in the converters and adapt the unknown parameters of the system. It also ensures the rapid tracking of the current references and regulates the DC-bus voltage for higher efficiency. Moreover, nonlinear stability analysis is done to promise the system stability while simulations are done in MATLAB/SIMULINK environment using the extra-urban driving cycle (EUDC) standard. An energy management algorithm has also been proposed to ensure effective power-sharing between the two sources depending upon their nature to improve the efficiency and life span of the HESS. In the simulation results, the proposed controller has been compared with controllers given in the literature to highlight its better performance in this application. Hardware-in-loop (HIL) test bench has also been used for the real-time implementation of the proposed controller to analyze its performance. Highlights: ATSMC has been designed for output voltage regulation of DC Bus of FC HEV. Asymptotic stability of the controller has been proved using Lyapunov Theory. Comparison is done with existing controllers using MATMLAB simulations. Hardware in the loop simulations are performed to validate the proposed controller.